The Anti-Inflammatory and Antioxidant Effects of Sodium Propionate - Filippone, Alessia (Int J Mol Sci, 2020)
The major end-products of dietary fiber fermentation by gut microbiota are the short-chain fatty acids (SCFAs) acetate, propionate, and butyrate, which have been shown to modulate host metabolism via effects on metabolic pathways at different tissue sites. Several studies showed the inhibitory effects of sodium propionate (SP) on nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway. We carried out an in vitro model of inflammation on the J774-A1 cell line, by stimulation with lipopolysaccharide (LPS) and H(2)O(2), followed by the pre-treatment with SP at 0.1, 1 mM and 10 mM. To evaluate the effect on acute inflammation and superoxide anion-induced pain, we performed a model of carrageenan (CAR)-induced rat paw inflammation and intraplantar injection of KO(2) where rats received SP orally (10, 30, and 100 mg/kg). SP decreased in concentration-dependent-manner the expression of cicloxigenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) following LPS stimulation. SP was able to enhance anti-oxidant enzyme production such as manganese superoxide dismutase (MnSOD) and heme oxygenase-1 (HO-1) following H(2)O(2) stimulation. In in vivo models, SP (30 and 100 mg/kg) reduced paw inflammation and tissue damage after CAR and KO(2) injection. Our results demonstrated the anti-inflammatory and anti-oxidant properties of SP; therefore, we propose that SP may be an effective strategy for the treatment of inflammatory diseases.